Katalog Official Merchandise “Noir666meters” - Muhamad Fauzan; Dini Faisal (Journal on Education, 2023)
Noir666meters is a stall that sells official merchandise for local bands in Indonesia, located in Padang City, West Sumatra. For now, noir666meters tends to sell its products only through social media, namely via Instagram, because the stalls are still too early to set up an offline shop, the available capital is also not sufficient to open a shop, therefore this design aims to design a catalog for the Noir666meters stalls. Where the appearance of the Noir666meters catalog as a media campaign in this writing can be easily recognized by the target audience and has an impact in increasing public awareness of Noir666meters stalls in West Sumatra, especially in the city of Padang. The method used in designing this catalog is 4D (Four-d) which has define, design, development, and desissment design stages. The solution to the problems in the design process starts with data analysis, documentation and interviews with the owner of Noir666meter. The design includes the main media in the form of a catalog starting from covering a rough layout, then a comprehensive layout, design validation, final product, and exhibition of the latest final work. So that the results obtained from 30 target audiences consisting of owners, DKV students, freelancers, students/students, and the public obtained results on the visual appearance aspect, the ease of receiving information, the ease of understanding information and the effectiveness aspect of the work with the conclusion of the results of the assessment aspect on a scale of 4-5 (satisfactory-very satisfying).